The tone was set in the past: Sustainability in new product development within the Icelandic marine industry - Bjarnveig Birta Bjarnadóttir 1992- (2020)
The marine industry in Iceland, with its history and foundation, has been referred to as a role model in the sustainable utilization of catch, especially when it comes to creating by-products. The purpose of this research was to investigate new product developments in the Icelandic marine sector regarding the three sustainability dimensions, namely environmental, economic, and social. The research also investigates how contextual factors influence product development alongside the sustainability agenda. In order to do so an explanatory sequential mixed methods design was used. The quantitative phase of the research investigated how the above-mentioned sustainability dimensions are represented in each phase of new product development in the Icelandic marine sector. Data for the quantitative phase was collected with a questionnaire. Then, a qualitative phase was implemented by collecting data from 11 interviews which aimed to further explain the quantitative findings. Quantitative results showed no statistical significance when comparing the different product stages in terms of level of sustainability commitment, across all three dimensions of sustainability. Qualitative results indicate that the historical foundation of the sector, along with informal working conditions and the emergence of synergy in informality, affect how the sustainability dimensions are represented in new product development. The research contextualizes suitability in new product development with respect to sustainability and also sheds light on how contextual factors influence the sustainability of new projects within the marine sector. These contextual factors are Icelandic history, Icelandic culture, the foundation of the marine industry, pillars of the marine industry, organizational culture and informal synergy. These results are particularly interesting from the perspective of marine industries in general, since they illustrate the importance of building an industry on a strong sustainable foundation. Furthermore, the results ...